2010
DOI: 10.1111/j.1532-7078.2010.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Individual Differences in Infant Visual Attention and Recognition Memory

Abstract: Past studies have identified individual differences in infant visual attention based upon peak look duration during initial exposure to a stimulus. Colombo and colleagues (e.g., Colombo & Mitchell, 1990) found that infants that demonstrate brief visual fixations (i.e., short lookers) during familiarization are more likely to demonstrate evidence of recognition memory during subsequent stimulus exposure than infants that demonstrate long visual fixations (i.e., long lookers). The current study utilized event-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 65 publications
(127 reference statements)
1
56
0
Order By: Relevance
“…Colombo and colleagues (Colombo, 1993; Colombo & Mitchell, 1990; Colombo, Mitchell, Coldren, & Freeseman, 1991; Colombo, Mitchell, & Horowitz, 1988) have shown that infants who demonstrate brief visual fixations (i.e., short lookers) during familiarization are more likely to demonstrate evidence of recognition memory during subsequent stimulus exposure than infants who demonstrate long visual fixations (i.e., long lookers). Reynolds, Guy, and Zhang (2011) reported that short-looking infants demonstrated significantly greater amplitude LSWs to novel compared to familiar stimuli indicative of recognition memory for the familiar object (see Figure 2). These memory effects occurred at both frontal and temporal electrodes for short lookers.…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 98%
See 4 more Smart Citations
“…Colombo and colleagues (Colombo, 1993; Colombo & Mitchell, 1990; Colombo, Mitchell, Coldren, & Freeseman, 1991; Colombo, Mitchell, & Horowitz, 1988) have shown that infants who demonstrate brief visual fixations (i.e., short lookers) during familiarization are more likely to demonstrate evidence of recognition memory during subsequent stimulus exposure than infants who demonstrate long visual fixations (i.e., long lookers). Reynolds, Guy, and Zhang (2011) reported that short-looking infants demonstrated significantly greater amplitude LSWs to novel compared to familiar stimuli indicative of recognition memory for the familiar object (see Figure 2). These memory effects occurred at both frontal and temporal electrodes for short lookers.…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 98%
“…However, significant changes in the amplitude of the LSW are routinely observed across repeated stimulus presentations or with increased familiarity. Thus, the LSW is believed to be associated with stimulus encoding and infant recognition memory (de Haan & Nelson, 1999; Reynolds, Guy, & Zhang, 2011; Nelson & Collins, 1991; Nelson & Collins, 1992; Snyder, 2010; Snyder, Webb, & Nelson, 2002; Snyder et al, 2010; Webb, Long, & Nelson, 2005; Wiebe et al, 2006). From 4 to 12 months, infants become increasingly more likely to demonstrate LSW correlates of recognition of a fully processed stimulus in response to previously encountered stimuli (Nelson & Collins, 1992; Nelson & deRegnier, 1992; Reynolds & Richards, 2011).…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 99%
See 3 more Smart Citations